2022
DOI: 10.3390/en15124396
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydrothermal Carbonization and Cold Atmospheric Plasma for Surface Modification of Brewer’s Spent Grain and Activated Carbon

Abstract: This paper presents results that show the effect of hydrothermal carbonization and subsequent cold plasma jet treatment with helium and argon on the structure and sorption properties of a material—spent brewery grain. Treatment of activated carbon, with a cold atmospheric plasma jet, was used comparatively. The effect of activation on the pore structure of the materials was carried out by the volumetric method at low pressure (N2, 77 K). The specific surface area as well as the total pore volume, average pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…An important advantage of plasma gasification with respect to different types of waste is its ability to perform vitrification [47]. The use of plasma for modification of the surface of different materials [48], including hydrochars, has also been reported [49][50][51][52][53]. Some authors also reported the use of plasma for the degradation of organic pollutants [54].…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of plasma gasification with respect to different types of waste is its ability to perform vitrification [47]. The use of plasma for modification of the surface of different materials [48], including hydrochars, has also been reported [49][50][51][52][53]. Some authors also reported the use of plasma for the degradation of organic pollutants [54].…”
Section: Introductionmentioning
confidence: 99%